1991
DOI: 10.1017/s0264180100000230
|View full text |Cite
|
Sign up to set email alerts
|

1. Trends in the provision of psychiatric care 1979–1988

Abstract: The aim of this chapter is to present data on psychiatric care provided to adult South-Verona residents over the 10-year period (1979–88) following the psychiatric reform and the implementation of a new community-based service. These data have been collected using the South-Verona Psychiatric Case Register (PCR), which started operating immediately after the establishment of the new service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 92 publications
2
16
0
1
Order By: Relevance
“…Thirty seven discrete-core studies report rates only for persons [31,33,45-49,55-57,59,61,65,71,73,75,76,78,79,85,86,88,91,93-96,99,103,104,107,112,114,121,124-126,180,190], 13 report rates only for males and females [41,50,52,53,67,74,82,102,111,116,123,188,189], and 18 studies report rates for persons, males, and females [13,51,54,58,60,69,70,72,77,80,83,84,92,97,98,100,101,106]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty seven discrete-core studies report rates only for persons [31,33,45-49,55-57,59,61,65,71,73,75,76,78,79,85,86,88,91,93-96,99,103,104,107,112,114,121,124-126,180,190], 13 report rates only for males and females [41,50,52,53,67,74,82,102,111,116,123,188,189], and 18 studies report rates for persons, males, and females [13,51,54,58,60,69,70,72,77,80,83,84,92,97,98,100,101,106]. …”
Section: Resultsmentioning
confidence: 99%
“…We identified 21 discrete-core studies with rates from urban sites [31,33,54,61,69-71,75,78,80,84,91,93,97,98,100,103,106,121,124,125], three studies from rural sites [57,59,60], and 42 studies with mixed urban-rural catchment areas [41,45-49],230,[50-53,55,56,58,65,67,72-74,76,77,79,82,83,85,86,88,92,94-96,99,101,102,104,107,111,112,114,116,123,188,189]. Two further studies provide rates for both urban and rural categories [13,126].…”
Section: Resultsmentioning
confidence: 99%
“…In Italy, Tansella et al reported its prevalence to be 1.3 for males and 1.1 for females per thousand. 22 In England, Freeman and Alpert found rates per thousand to be 7.0 in males and 6.6 in females. 23 …”
Section: Discussionmentioning
confidence: 99%
“…It developed during the dawn of the deinstitutionalization era in the 1960s and has been rapidly expanding during the last decade. Outcome measures have been predominantly used to evaluate the effects of major changes in the health care system (Wing, 1972;Nielsen et al, 1981;Hafner et al, 1980;Tansella et al, 1991) and to compare the outcomes of different mental health care systems (Sytema, 1994;Sytema et al, 1989) and programs (Test et al, 1978). Unfortunately, the results of mental health service research have rarely made a major impact on the political arid administrative level of planning and development of mental health services.…”
Section: Helle Charlotte Knudsenmentioning
confidence: 99%